Currency Diversification of Reserves and Sovereign Debt for Small Open Economies - Rajasingham, Indi (IMF Working Papers; Working Paper, 1991)
An approach for minimizing risk through diversification of foreign exchange reserves and sovereign borrowings is proposed for central banks of small open economies. This approach--developed in a simple 2-period, 3-country framework--differs from past work in that the elements of exchange and price risk associated with trade and payments are considered in the portfolio allocation problem. The analysis shows that the net level of reserves and the primary transactions balance affect the optimal portfolio leading to deviations from the optimal allocation prescribed by the classical portfolio model. In addition, this result has implications for the currency composition of exchange market intervention transactions.